MAJOR EFFECTS OF HERDSMEN AND CROP FARMERS CONFLICTS ON EXTENSION SERVICE DELIVERY AND MITIGATIONS IN RURAL COMMUNITIES IN SOUTH-EAST ZONE, NIGERIA. - Uke, P.C,; Ugwu, J.N,; Nneji P C, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2025)
This study was on the major effects of herdsmen and crop farmers conflicts on extension service delivery in Rural Communities of South East, Nigeria and likely mitigations.. Objectives of the study were; to examine the socio economic characteristics of farmers and herders in the study area, socio economic and environmental factors influencing the conflicts,ascertain the effects of farmers and herders conflicts on extension services in the study area, examine the major causes of the conflicts, identify strategies for sustainable coexistence of herdsmen and farmers in the study area. A combination of purposive and simple random sampling techniques were employed in the selection of 254 respondents (180 farmers and 24 herdsmen). Also interviewed were 50 Extension agents. Primary data were sourced through field survey with the aid of a well-structured questionnaire and interview schedule. Descriptive statistics were employed in data analysis. The result of data analysis showed that destruction of the farmers’ crops by cattle was the greatest source of conflict (89.4%) followed by contamination of sources of potable water (66.3%). Other activities of herdsmen that caused conflict as perceived by the crop farmers were plucking of fruits, cutting of bamboo for their tent making and defecation along the road and playing grounds. The result also showed that the conflicts seriously affected extension services in the study area as it disrupted T and V extension system ,39%, farmers participation, increased fear.Based on the herdsmen, the major causes of conflicts were hitting of the cattle by farmers (100%), followed by injuring and killing of the cattle (87.5%). However, raping of Fulani girls or women wasnot experienced by the Fulani community in the area. Other sources were abusing and cursing of Fulani herdsmen and blocking of roads by crop farmers. Identified consensus Mitigational intervention options for sustainable peaceful coexistence among the farmers and herders included encouraging herdsmen to learn the custom of their host community, compensation of aggrieved farmers and herders, punishment of the offenders, educating farmers and herdsmen on their interdependence and institution of a regular meeting of herdsmen and community leaders’. The study concluded that the institution of stake holders to oversee the compensation of the aggrieved was very necessary. It also concluded that compensation of the aggrieved herders or farmers and punishment of the offenders should be an imperative mitigational measure. Recommendations such as restricting herdsmen to their own communities, provision of grazing reserves, as well as restricting herdsmen to particular locations were made, among others